Plantar shear stress distributions in diabetic patients with and without neuropathy - Yavuz, Metin (2013)
BACKGROUND: The exact pathology of diabetic foot ulcers remains to be resolved. Evidence suggests that plantar shear forces play a major role in diabetic ulceration. Unfortunately, only a few manuscripts exist on the clinical implications of plantar shear. The purpose of this study was to compare global and regional peak plantar stress values in three groups; diabetic patients with neuropathy, diabetic patients without neuropathy and healthy control subjects. METHODS: Fourteen diabetic neuropathic patients, 14 non-neuropathic diabetic control and 11 non-diabetic control subjects were recruited. Subjects walked on a custom-built stress plate that quantified plantar pressures and shear. Four stress variables were analyzed; peak pressure, peak shear, peak pressure-time and shear-time integral. FINDINGS: Global peak values of peak shear (p=0.039), shear-time integral (p=0.002) and pressure-time integral (p=0.003) were significantly higher in the diabetic neuropathic group. Local peak shear stress and shear-time integral were also significantly higher in diabetic neuropathic patients compared to both control groups, in particular, at the hallux and central forefoot. Local peak pressure and pressure-time integral were significantly different between the three groups at the medial and lateral forefoot. INTERPRETATION: Plantar shear and shear-time integral magnitudes were elevated in diabetic patients with peripheral neuropathy, which indicates the potential clinical significance of these factors in ulceration. It is thought that further investigation of plantar shear would lead to a better understanding of ulceration pathomechanics, which in turn will assist researchers in developing more effective preventive devices and strategies.